2013
DOI: 10.1136/jmedgenet-2012-101282
|View full text |Cite
|
Sign up to set email alerts
|

Asphyxiating thoracic dysplasia: clinical and molecular review of 39 families

Abstract: belongs to the short rib polydactyly group and is characterized by a long and narrow thorax, short long bones and trident acetabular roof. Polydactyly, retinal degeneration, cystic renal and liver diseases have been occasionally reported. Today, mutations in IFT80 (MIM 611177), DYNC2H1 (MIM 603297), TCC21B (MIM 612014) and WDR19 (MIM 608151) genes have been reported in ATD. Through a national grant (PHRC, AOM 06031), we have collected 55 ATD cases including 29 fetuses issued from 42 families who benefit the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 12 publications
3
90
0
2
Order By: Relevance
“…Sensenbrenner patients with mutations were more likely to have sagittal craniosynostosis, joint laxity, dental anomalies, retinal abnormalities, and congenital heart defects. As expected, considerable overlap with ATD-JS was noted, but the distinctive Sensenbrenner facial appearance (dolichocephaly, high hairline, forehead bossing), sagittal craniosynostosis, ectodermal anomalies (teeth, hair, nails), and syndactyly appear to differentiate the two syndromes [Keppler-Noreuil et al, 2011;Baujat et al, 2013]. Severe forms of Sensenbrenner syndrome and ATD-JS have been diagnosed as short rib-polydactyly syndromes (SRPs).…”
Section: Comparison Of Manifestationsmentioning
confidence: 57%
See 3 more Smart Citations
“…Sensenbrenner patients with mutations were more likely to have sagittal craniosynostosis, joint laxity, dental anomalies, retinal abnormalities, and congenital heart defects. As expected, considerable overlap with ATD-JS was noted, but the distinctive Sensenbrenner facial appearance (dolichocephaly, high hairline, forehead bossing), sagittal craniosynostosis, ectodermal anomalies (teeth, hair, nails), and syndactyly appear to differentiate the two syndromes [Keppler-Noreuil et al, 2011;Baujat et al, 2013]. Severe forms of Sensenbrenner syndrome and ATD-JS have been diagnosed as short rib-polydactyly syndromes (SRPs).…”
Section: Comparison Of Manifestationsmentioning
confidence: 57%
“…We noted any type of eye problem more commonly in the patients with a mutation (21% vs. 12%), which compares to ATD-JS, and Joubert syndrome. Baujat et al [2013] observed a 50% frequency of eye problems in their patients with ATD-JS ($65% of whom had mutations in either DYNC2H1 or IFT80) who had systematic eye evaluations in their patients.…”
Section: Certain Disorders Listed Onmentioning
confidence: 98%
See 2 more Smart Citations
“…JATD is a rare autosomal recessive skeletal dysplasia with short limbs, narrow thorax, trident acetabular roof, and occasional polydactyly (107). Studies have suggested that mutations of Ift80, DYNC2H1, TTC21B (encoding Ift139) and WDR19 (encoding Ift144) are associated with JATD (33, 35, 40, 108110). Respiratory failure is the usual cause of death in JATD in early infancy (110).…”
Section: Cilia/ift Protein and Motor-related Human Diseasesmentioning
confidence: 99%